Controle estatístico de processo aplicado ao monitoramento de perdas na colheita mecanizada de cana-de-açúcar - Torres, Luma Stefania [UNESP] (2014)
In the sugarcane production chain, the sugarcane process for mechanized harvesting is considered one of the greatest economic bottlenecks, showing low levels of operational efficiencies and high levels of losses. To assist the improvement in harvesting processes and procedures you can adopt quality controls improving harvesting operations and by reducing the levels of losses. The objective of this work was to evaluate the losses at harvest data collected during two harvest season analyzing five teams. The losses data were collected in 9 months of the 2012/2013 and 9 months of the 2013/2014 harvest season by the harvest quality team. The losses were subdivided into: stubbles, stalks, splinted stalks, untied and fixed piece, whole cane, cane top, splint and total each team separately. The loss data were subdivided weekly, totaling 40 weeks of harvest, and the statistical analyses were using Minitab 16® software. The values of losses generated curves with asymmetrical features positive leptokurtic. Almost all coefficients of variation were high showing a large variability among the data collected and harvest losses indexes. With regard to the values of harvest losses, all indexes remained out of control for all teams, however the results were considered within acceptable loss rates for Brazilian Sugarcane mills